(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the treatment outcomes of simple dilatation procedure for the management of short segment uretheral strictures. Study Design: Retrospective/observational study Place and Duration of Study: This study was conducted at the Saidu Teaching Hospital Swat and PIMS Hospital Islamabad during from June 2019 to November 2019. Materials and Methods: Total 104 patients presented with simple short segment urethral strictures were included. Patients detailed demographic including age, sex, clinical presentation and etiology of strictures were recorded after written consent. All patients receive simple urethral dilatation with antibiotics under local anesthesia. Pre and postoperative maximum flow rate on uroflowmetry and post-void residual urine (PVR) were recorded. Follow-up was taken at 4, 12 weeks and at 1 year. Overall improvement and recurrence rate was examined at final follow-up. Results: The mean age of patients was 38.52+11.46 years. Majority of patients 80 (78.85%) had weak urine stream. 90 (86.54%) patients had iatrogenic strictures and 14 (13.46%) had idiopathic strictures. There is a significant improvement regarding maximum flow rate and PVR at 1, 3 and 6 months postoperatively with p-value 0.0001. At final follow-up, 95 (91.34%) patients showed full improvement. Recurrence found in 9 (8.65%) patients. Conclusion: Simple dilatation under antibiotics cover is safe and effective treatment modality with fewer complications rate.